1989
DOI: 10.1353/sls.1989.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Reception of Signs in Peripheral Vision by Deaf Persons

Abstract: To test whether deaf persons can read signs in peripheral vision, 12 profoundly deaf students, aged 15 to 18, in a residential school for the deaf, were seated between two signers, who presented common signs in random turns. Subjects responded by signing back to a video-camera, on which they were to fix their gaze. The tape recorded their responses as well as their eye movements, if any. Twenty-four signs were presented in each of two conditions: with the stimulus signs between 45° and 61° in the periphery, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
3
16
0
1
Order By: Relevance
“…This has been attributed to strong social norms which produce an “eye primacy effect” (Gullberg and Holmqvist, 1999; Lansing and McConckie, 1999). This gaze behavior has also been reported in deaf people perceiving sign language (Siple, 1978; Muir and Richardson, 2002; Agrafiotis et al, 2003; Emmorey et al, 2009), and is thought to be because large moving targets, such as signs in sign languages, are successfully perceived through peripheral vision (Swisher et al, 1989). The visual area from which useful information can be obtained, including central foveal vision (i.e., what a fixation measure would register) and peripheral vision, is referred to as the “useful visual field” (Saida and Ikeda, 1979).…”
Section: Introductionsupporting
confidence: 59%
“…This has been attributed to strong social norms which produce an “eye primacy effect” (Gullberg and Holmqvist, 1999; Lansing and McConckie, 1999). This gaze behavior has also been reported in deaf people perceiving sign language (Siple, 1978; Muir and Richardson, 2002; Agrafiotis et al, 2003; Emmorey et al, 2009), and is thought to be because large moving targets, such as signs in sign languages, are successfully perceived through peripheral vision (Swisher et al, 1989). The visual area from which useful information can be obtained, including central foveal vision (i.e., what a fixation measure would register) and peripheral vision, is referred to as the “useful visual field” (Saida and Ikeda, 1979).…”
Section: Introductionsupporting
confidence: 59%
“…This would leave the comparatively clear asserted portions underneath tense to peripheral portions of their gaze. And indeed, as pointed out by Swisher, Christie & Miller (1989), signers typically focus on each other's faces, not on each other's hands during conversation. We are quite confident that the organizing principles we have laid out in this paper may prove useful for the analysis of a variety of further phenomena in sign languages generally.…”
Section: Discussionmentioning
confidence: 98%
“…This ®nding is clearly relevant to our ®nding that Deaf interactants are able to organise their talk in terms of a collaborative model. Swisher et al (1989) found that signers in experimental circumstances were able to perceive single sign utterances articulated at 618 to 778 in the periphery with a mean accuracy of 68 percent. They point out that extra information perceived in the periphery can allow addressees to monitor the rest of the group while maintaining the gaze on the current signer (or signers).…”
Section: The Collaborative Floor In Deaf Friends' Talkmentioning
confidence: 95%
“…Addressees may use regulators to signal that they accept the signer's right to the¯oor and are ready to receive the signing (see also Smith 1999; Smith and Sutton-Spence in press). Similarly, Siple (1978) and Swisher, Christie and Miller (1989) in their work on peripheral vision in Deaf interaction discuss the social norm requiring that the addressee or addressees maintain eye gaze on the signer's face during signing.…”
Section: Turn-taking In Conversationmentioning
confidence: 99%